I'm stuck on the very last question (11b) of the calculator paper from 2001. Anyone kind enough to help?

**0**

# 2001 paper 2 Question 11b

Started by HatingHighers, Mar 21 2005 07:43 PM

6 replies to this topic

### #1

Posted 21 March 2005 - 07:43 PM

### #2

Posted 21 March 2005 - 07:59 PM

This is hard! Im not sure myself. I cant do it but this is what I have done so far.

If you dont know, the final answer is

This is what I have done:

y=x+p

gradient = 1

If you differentiate y = p + (p-1) - x and work out that gradient, i get

y = p - 1 - 2x

If its a tangent then the gradients are the same.

m = p - 1 - 2x

p = 2x

Some how the x must vanish. Havnt worked out how though.

Hope this is a help. Sorry I have not managed to do it lol. What have you done so far?

If you dont know, the final answer is

**2**!This is what I have done:

y=x+p

gradient = 1

If you differentiate y = p + (p-1) - x and work out that gradient, i get

y = p - 1 - 2x

If its a tangent then the gradients are the same.

m = p - 1 - 2x

p = 2x

Some how the x must vanish. Havnt worked out how though.

Hope this is a help. Sorry I have not managed to do it lol. What have you done so far?

### #3

Posted 21 March 2005 - 08:07 PM

I got it to where you did, lol

I got this:

dy/dx = p - 1 - 2x

m = 1, so

p-1-2x = 1

p = 2x + 2

Then I got stuck...

I got this:

dy/dx = p - 1 - 2x

m = 1, so

p-1-2x = 1

p = 2x + 2

Then I got stuck...

### #5

Posted 21 March 2005 - 08:23 PM

Equation of curve: y = p + (p -1) - x

Equation of line: y = x + p

If it's a tangent then both lines are equal to each other.

p + (p -1) - x

p + px - x -x

x

Since there is a tangent b

x

x

a = 1

b = 2 - p

c = 0

b

(2 - p)

(2 - p)(2 - p) = 0

Hope that helps...

^{2}Equation of line: y = x + p

If it's a tangent then both lines are equal to each other.

p + (p -1) - x

^{2}= x + pp + px - x -x

^{2}= x + px

^{2}+ 2x - px = 0Since there is a tangent b

^{2}- 4ac = 0 for equal roots.x

^{2}+ 2x - px = 0x

^{2}+ x(2 - p) = 0a = 1

b = 2 - p

c = 0

b

^{2}- 4ac = 0(2 - p)

^{2}- 4(1)(0) = 0(2 - p)(2 - p) = 0

**p=2**Hope that helps...

| Help yourselves and others - HSN Contribute | Spread the Word!

| PPA Hints | Chemistry Formulae | H Maths Links |

| PPA Hints | Chemistry Formulae | H Maths Links |

### #7

Posted 14 April 2005 - 05:27 PM

same!!

beast

#### 1 user(s) are reading this topic

0 members, 1 guests, 0 anonymous users